UTILIZING OF E-LEARNING MEDIA TO INCREASE AUTONOMY AND BRAINWORK OF BIOLOGY STUDY IN CLASS XI SCIENCE 3 MAN 2 MODEL PEKANBARU ACADEMIC YEAR 2010/2011 - Zulfarina '; Mariani Natalina; Tri Nova Anggraini (Biogenesis, 2011)
A class action research has been done to increase autonomy and brainwork of biology study in class XI Science 3 MAN 2 Model Pekanbaru by using e-learning. This research started on October until December 2010. The subjects of this research were all the students of class XI Science 3 MAN 2 Model Pekanbaru, consists of 11 boys and 18 girls. The parameters on this research are autonomy, brainwork, and student activity. Before using e-learning, the average of student autonomy was 3.25 (enough), after being used e-learning at cycle I, the average of student autonomy is 3.76 (high) and on cycle II increased to 4.11 (high). Brainwork was evaluated from student reservation and study finishing. At cycle I student reservation was 68.45 (less) and at cycle II was 89.47 (increased). Student study finishing increased, which at cycle I was 84.56% (good) to 88.72% (good) at cycle II. From the results of this research concluded that utilizing of e-learning can increase autonomy and brainwork of students from class XI Science 3 MAN 2 Model Pekanbaru academic year 2010/2011.